Synthesis and Characterization of a Porous Ga2O3 Material with a Low Dielectric Constant - Dong, Xue; Woo, Chaeheon; Yoo, Chan-Sei; Kim, Tae Yeong; Zhang, Xiaojie; Kim, Yeongjin; Kang, Jinsu; Jeon, Jiho; Bang, Hyeon-Seok; Kim, Youngho; Park, Jae-Hyuk; Yu, Hak Ki; et al. (American Chemical Society, 2024)
In the context of contemporary wireless communication technologies, operational frequencies have considerably escalated. Consequently, the demand for dielectric ceramics with low dielectric constants and minimal losses has become imperative in the field. Thermally stable beta-Ga2O3 was synthesized by a simple chemical precipitation route followed by calcination, making it a promising candidate for microwave applications. The as-prepared beta-Ga2O3 maintained a pore structure with a width of 20.943 nm. Notably, the material exhibited early-stage sintering at relatively low temperatures, around 900 degrees C, due to these pores. The as-prepared beta-Ga2O3 ceramics exhibited outstanding dielectric properties, featuring a lower epsilon(r) value of 3.2168 and a low dielectric loss of 0.000795 at 9.4 GHz. The lower epsilon(r) contributes to minimized time delays, while the low dielectric loss enhances the signal selectivity. These findings establish beta-Ga2O3 as a suitable material for electronic packaging in microwave applications.